2009
DOI: 10.1787/eco_studies-v2009-art4-en
|View full text |Cite
|
Sign up to set email alerts
|

Improving public spending efficiency in primary and secondary education

Abstract: Influenced by the perceived link between higher levels of educational attainment and growth, the education sector has seen significant reform efforts in recent years in a number of countries. Public spending in this sector has increased on average by one-fifth in real terms over the past decade and growth in terms of spending per student has also been marked in many countries (Figure 1, upper panel); governments in the OECD area now spend on average around 3% of GDP on primary and secondary education. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 6 publications
1
48
0
2
Order By: Relevance
“…The relationship between spending on education and schooling performances has proven to be weak at the international level and in many OECD countries (Sutherland et al, 2009;OECD, 2007c). Despite a real spending per pupil increase of 4.8% annually between 1997 and 2010, assessments of cognitive improvements are mixed.…”
Section: Box 3 Improving Educational Outcomes and Raising Skillsmentioning
confidence: 99%
“…The relationship between spending on education and schooling performances has proven to be weak at the international level and in many OECD countries (Sutherland et al, 2009;OECD, 2007c). Despite a real spending per pupil increase of 4.8% annually between 1997 and 2010, assessments of cognitive improvements are mixed.…”
Section: Box 3 Improving Educational Outcomes and Raising Skillsmentioning
confidence: 99%
“…Intuitively, this would seem to break a critical link between accountability and autonomy, restricting school leaders' freedom to pay more to attract and keep good teachers, or more broadly to allocate school resources among competing uses in line with student needs. OECD empirical work has found that student attainment is higher when schools have autonomy over teacher salaries and pay progression (Sutherland et al, 2009). PISA work further suggests that many well performing education systems have moved from bureaucratic "command and control" towards school systems where considerable discretion is given to school heads and faculties in how resources are allocated, a factor which is shown to be closely related to school performance when combined with effective accountability systems; school autonomy in defining and elaborating curricula and assessments also relates positively to system performance (OECD, 2010a, pp.…”
Section: Schooling: Maintaining Engagementmentioning
confidence: 99%
“…Choice and competitive efficiency are also limited by the still small share of alternatives to the state school system. Indeed, a larger share of private government-dependent schools has been shown to enhance system performance in OECD countries (Sutherland et al, 2009). The government is planning to introduce a few charter schools in mid-2013 on a trial basis.…”
Section: Schooling: Maintaining Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among the latter, the most relevant draw on information provided by the OECD's PISA program as they compare from different perspectives the efficiency with which the education systems of different countries operate. For example, Afonso and Aubyn (2005;2006) and Sutherland et al (2009) analyze the efficiency of public spending on education for a group of OECD countries, and emphasize the role played by the institutions of each country in accounting for the disparity in the results reported. The influential role played by a country's institutions is similarly stressed by De Jorge and Santín (2010), who, like Deutsch et al (2013), consider an analysis of efficiency at the student level as the best approach to optimize the use of available information.…”
Section: Introductionmentioning
confidence: 99%